Inorganic arsenic exposure during pregnancy affects post-natal growth, blood parameters, and organ development of mice offspring - Md. Khayrul Basher; Sumon Sarkar; Md. Hosne Mobarak; Md. Rashedul Islam (Journal of Advanced Biotechnology and Experimental Therapeutics, 2023)
Arsenic is a potentially toxic agent for human health due to its widespread presence in the environment. Arsenic poisoning from drinking contaminated groundwater has become one of Bangladesh's most difficult healthcare problems. However, there is a lack of understanding of the detrimental impact of arsenic toxicity on children of arsenic-exposed parents. This study evaluates the effect of arsenic toxicity on body growth, blood parameters, and organ development of F1 mice. In this study, adult female mice were exposed to sodium arsenite from gestation day 12.5 until parturition, and then the postnatal growth, blood indices, and organ development were assessed. The result showed that from birth to weaning offspring of the sodium arsenite-treated group exhibited significant (p [ J Adv Biotechnol Exp Ther 2023; 6(2.000): 445-457]